Medical education : developing a curriculum for practice - Fish, Della (Open University Press, 2005)
What are the contemporary problems facing curriculum designers and developers? What are the key questions that ought to be addressed with regard to curriculum design for medical practice? How might a curriculum for practice in medical education be developed? "Medical Education" offers a detailed response to these questions and shows what form a curriculum for practice should take and how one can be developed. These ideas are presented in a highly practical and readable account that is essential reading for those involved in educating the doctors of the future and for policy makers in the field of medical education. It also offers useful advice for those in related fields of health care. The authors show that recent developments of curricula for postgraduate doctors have been founded on the misguided view (promoted by politicians and policy makers) that medical practice is routine, straightforward and able to be reduced to simple protocols that professionals must learn and follow. In this view, doctors are technicians who need merely to be trained through a simple curriculum.; In contrast, this book shows that the practice of medicine as experienced by working doctors is complex, uncertain and unpredictable. This requires a curriculum that provides the opportunity to learn to exercise professional judgement and make decisions based on practical wisdom.